1997
DOI: 10.1021/ac970123a
|View full text |Cite
|
Sign up to set email alerts
|

Calibration of Micropipets Using the Bioluminescent Protein Aequorin

Abstract: A new method for calibrating micropipets and determining accurate injection volumes using a pressure-based injector has been developed. This method employs the bioluminescent protein aequorin and can be used to determine injection volumes as small as 3 pL. The calibration plots are linear over at least 3 orders of magnitude. In contrast to conventional micropipet calibration methods that employ fluorescent molecules, the present method produces small background signals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…It has also been used as a highly sensitive label in binding assays (8)(9)(10)(11)(12) and in the detection of proteolytic bond cleavage (13). Aequorin can be detected in the femtomole to attomole range, which has allowed its employment as an alternative label to fluorescent probes in the calibration of micropipets (14). This photoprotein offers several advantages such as no photobleaching and the production of signal with virtually no background.…”
Section: Introductionmentioning
confidence: 99%
“…It has also been used as a highly sensitive label in binding assays (8)(9)(10)(11)(12) and in the detection of proteolytic bond cleavage (13). Aequorin can be detected in the femtomole to attomole range, which has allowed its employment as an alternative label to fluorescent probes in the calibration of micropipets (14). This photoprotein offers several advantages such as no photobleaching and the production of signal with virtually no background.…”
Section: Introductionmentioning
confidence: 99%
“…One important factor in the performance of an assay in such small volumes is the amount of error that is introduced during the delivery of the assay components. Previous results have indicated that the single largest source of error in these assays lies in microinjection of the reagents. For this reason, we developed a protocol minimizing the number of injections necessary to perform the assay. This involves first injecting the AEQ−biotin (and free biotin, if needed) from one micropipet, followed by injection of the avidin mixed with Ca 2+ from a second micropipet.…”
Section: Resultsmentioning
confidence: 99%
“…BF 100-78-15) having an outside diameter of 1.0 mm and an inside diameter of 0.78 mm. Volume determination experiments are described in detail in ref 36. Briefly, injection volume was determined by measuring the diameter of the bubble created upon injection of the aqueous reagent into microscope immersion oil.…”
Section: Experimental Protocolmentioning
confidence: 99%
“…So, in chemiluminescence the problems such as source instability and backgrounds noise are resolved. 4 Furthermore, chemiluminescence labeling which is commonly used in immunoassays has advantages such as fast light emission, 5 high sensitivity and safety, a controllable emission rate and low cost. In addition, conjugation makes the chemiluminant reagents more stable and also luminometers based on photomultiplier tubes are available.…”
Section: Introductionmentioning
confidence: 99%